A intertextualidade como estratégia argumentativa nos artigos de Luiz Felipe Pondé - Silveira, Ana Cláudia Ferreira da (2015)
The present dissertation aims at presenting an analysis of the rhetorical-argumentative procedures used by the Brazilian philosopher and columnist Luiz Felipe Pondé in his opinion articles. Through this present analysis, we shall try to identify the rhetorical style of the columnist. In addition, we intend to verify in which way the rhetorical elements (ethos, pathos and logos) act in the construction and characterization of the journalistic opinion piece genre. Aiming at proceeding with the analysis, four articles published in Folha de S.Paulo newspaper, during the 2012-2014 biennium, have been selected. Concerning the selected samples, we hope to have ensured the representativeness character and obtained, through their data and recurrence, the indicating and characterizing elements of the articles written by the columnist in totality. For the present paper, regarding the rhetorical and argumentative studies, we have selected the following authors as our theoretical reference: Aristotle (2012); Perelman & Olbrechts-Tyteca (2005); Perelman (2004); Reboul (2004); Meyer (1998, 2007); Breton (2003) and Plantin (2008). Regarding the discussion on the corpus, especially concerning the genre at issue, some statements made by the journalism theoretician Melo (2003) have been taken into consideration. Furthermore, aiming at elucidating the relation between rhetoric and opinion journalism, more specifically journalistic opinion pieces, the research of Santamaría Suárez and Casals Carro (2000) has been used. It seems relevant to promote a study which contemplates the selected genre under the theoretical perspective of rhetoric due to the fact that one of the main goals of this genre is the formation and/or modification of public opinion, that is to say, the auditorium/reader adhesion to the presented ideas. It is possible to conclude that, through the analysis of the corpus, we were able to verify the recurrence of certain rhetorical-argumentative elements, thus, able to identify the rhetorical procedure which was used as the organizing principle for Luiz Felipe Pondé texts, which is: the intertextuality. In addition, the present study has reached the objective of perceiving the action of the three rhetorical proofs (ethos, pathos and logos) in the selected genre. Keywords: argumentation and rhetoric; journalistic opinion piece; intertextuality; Luiz Felipe Pondé.